Key decision-makers' perceptions of sustainable sea fisheries in Namibia and the implications for environmental education programmes - Boois, Ulrich (Rhodes University, Faculty of Education, Department of Education, 2000)
This study investigates key decision-makers' perceptions of sustainable sea fisheries in Namibia, and explores the possibilities for the future development of education programmes that focus on "sustainability" in the fisheries sector. The concept of "sustainability" and its application in the context of a biological resource, namely sea fisheries, was examined. A series of questions were raised concerning sustainable fisheries: intergenerational implications of patterns of resource use, equity concerns, time horizons, and the protection of marine biodiveristy, among others. Examples from the Namibian and the European Community Sea Fisheries Industries are used to illustrate these issues. In spite of divergent views on what "sustainability" means, the study leads to certain findings that have broader policy implications. Data was collected from semi-structured interviews undertaken with six (6) key decision-makers in the Sea Fisheries Industry of Namibia, then analysed and assessed. The perceptions of key decisionmakers were determined by qualitative analysis in the interpretive paradigm. The data indicated some agreement in terms of what the key decision-makers think about the sustainable utilisation of the fisherjes resources. It is almost impossible to have complete agreement, because the decision-makers are from different contextual backgrounds. Those who make the decisions are more concerned about "how to manage" and those who act on the decisions put more emphasis on economic self-interest. Although the interviewees' perceptions of sustainable fisheries was imperfect, there was broad support for its aims and principles. The study also revealed that the achievement of sustainable sea fisheries development in Wamibia will require broader educational and public awareness programmes to enhance participation in decision-making debates. Formal and informal marine environmental education, from the perspective of "Responsible Fishing" has been emphasised.
Keywords: Environmental education -- Namibia; Fisheries -- Environmental aspects; Fisheries -- Environmental aspects -- Namibia; Sustainable development -- Environmental aspects; Sustainable development -- Environmental aspects -- Namibia